2013
DOI: 10.2196/jmir.2161
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals' Expectations Versus Experiences of Internet-Based Telemonitoring: Survey Among Heart Failure Clinics

Abstract: BackgroundAlthough telemonitoring is increasingly used in heart failure care, data on expectations, experiences, and organizational implications concerning telemonitoring are rarely addressed, and the optimal profile of patients who can benefit from telemonitoring has yet to be defined.ObjectiveTo assess the actual status of use of telemonitoring and to describe the expectations, experiences, and organizational aspects involved in working with telemonitoring in heart failure in the Netherlands.MethodsIn collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 23 publications
2
45
1
Order By: Relevance
“…Because of increasing patient volumes, routine follow-up contributes a significant burden to already overstrained clinics in terms of time, capital, and human resources required, and to patients and caregivers in terms of travel and time. Remote monitoring allows assessment of device function [3] and patients’ HF-related parameters at home [4], and may represent a safe, effective, and cost-saving way to significantly reduce in-office follow-up visits that are a burden for both hospitals and patients [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Because of increasing patient volumes, routine follow-up contributes a significant burden to already overstrained clinics in terms of time, capital, and human resources required, and to patients and caregivers in terms of travel and time. Remote monitoring allows assessment of device function [3] and patients’ HF-related parameters at home [4], and may represent a safe, effective, and cost-saving way to significantly reduce in-office follow-up visits that are a burden for both hospitals and patients [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In the study of De Vries et al, high expectations for telemonitoring were reported, but HCPs expectations after implementing RTM were not met [1]. This lack of experience with RTM, but at the same time having a positive attitude towards using RTM for patients with HF, places a large responsibility for applying good implementation strategies in the future.…”
Section: Discussion Principal Resultsmentioning
confidence: 99%
“…Remote patient telemonitoring (RTM) is defined as "the remote monitoring of patients including use of audio, video, other telecommunication and electronic information processing to monitor patient status at a distance" [1]. With heart failure (HF) patients, RTM can be used to perform early detection of decompensation at home, prevent unnecessary healthcare utilization, and decrease health care costs [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…158 Monitoring of fluid accumulation via an implanted device is another approach, but requires further development for routine daily use. 159 A survey of heart failure clinics in the Netherlands showed that telemonitoring did not deliver the anticipated benefits in terms of patient care, reduced workload or lower treatment costs, 160 suggesting that attention should also be paid to how systems are implemented.…”
Section: Use Of Technology In Heart Failure Managementmentioning
confidence: 99%